Analysis of Vibration and Noise on Vibrating Screen at PT. Mifa Bersaudara - Herdi Susanto; Kamarullah (LPPM Politeknik Aceh Selatan, 2021)
The purpose of this study was to analyze the level of vibration and noise on the Equipment Vibrating screen crusher FC 02 at PT. MIFA Bersaudara. Vibration is measured using a vibration meter, noise is measured by a digital sound level meter. Measurements are made on the x, y and z axes at each measurement point. The results showed that the value of the vibration level on the Vibrating screen crusher FC 02 on the x-axis with the velocity value of 28.56 mm/s, the y-axis value of 29.82 mm/s and the z-axis velocity value of 25.46 mm/s. While the Acceleration value on the x-axis is 20.7 m/s 2 the value is 30.86 m/s 2on the y and z axes of 21.42 m/s 2 . While the noise value indicates that the average value on the right side is 99.6 dBA on the right side and 101.7 dBA on the left side. Efforts were made to overcome the problem, namely by not operating the VSC FC 02 exceeding the recommended maximum limit of 60 dBA and the maximum allowed which is 70 dBA so as to prevent problems of comfort, health, and safety at work. Operators and employees are advised to stay at the location for no more than 15-30 minutes, if more than that time must use safety earmuffs.